2015
DOI: 10.1089/omi.2015.0047
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Disease Progression and Survival in an Adult Population in Zimbabwe: Is There an Effect of the Mannose Binding Lectin Deficiency?

Abstract: HIV infection remains a major global health burden since its discovery in 1983. Sub-Saharan Africa is the region hardest hit by the HIV/AIDS pandemic where 63% of the 33 million infected people live. While there is marked person-to-person variability in susceptibility, progression, and survival with HIV infection, there is a paucity of predictive diagnostics associated with these clinical endpoints. In this regard, the deficiency in plasma Mannose Binding Lectin (MBL) is a common opsonic defect reported to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 63 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…Human immunodeficiency virus (HIV) infection/acquired immunodeficiency syndrome (AIDS) remains a major health burden, especially in sub-Saharan Africa where 63% of the 33 million globally infected people live. 1 The registration of >400 000 new HIV infections in South Africa in 2012, 1 places this country at the forefront of the HIV burden worldwide, with KwaZulu-Natal as the epicentre of the AIDS pandemic. 2,3 The last three decades have witnessed the emergence of a heterogeneous range of HIV-associated vascular pathologies under the rubric of "HIV-associated vasculopathy", the pathophysiology of which remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Human immunodeficiency virus (HIV) infection/acquired immunodeficiency syndrome (AIDS) remains a major health burden, especially in sub-Saharan Africa where 63% of the 33 million globally infected people live. 1 The registration of >400 000 new HIV infections in South Africa in 2012, 1 places this country at the forefront of the HIV burden worldwide, with KwaZulu-Natal as the epicentre of the AIDS pandemic. 2,3 The last three decades have witnessed the emergence of a heterogeneous range of HIV-associated vascular pathologies under the rubric of "HIV-associated vasculopathy", the pathophysiology of which remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the -550, -221 and exon 1 polymorphisms were studied simultaneously in PLWHA and showed no impact on viral load or TCD4 count [ 53 ], and they were also not associated with viral load, TCD4 count, disease progression, or survival of a population of PLWHA from Africa who was not under antiretroviral therapy [ 28 ]. However, the present study simultaneously evaluated the three main polymorphisms of the MBL2 gene and the high, intermediate and low expression haplotypes and found an association between the HIV/HHV-8 coinfected patients who had the intermediate expression haplotype with TCD4 count when compared with patients monoinfected by HIV.…”
Section: Discussionmentioning
confidence: 99%
“…The progression of the disease caused by HIV infection is characterized by a decline in TCD4 cell count and an increase in viral load, leading to patient death in the absence of antiretroviral therapy [ 28 ]. Thus, some studies suggest that in HIV/HHV-8 coinfection, severe depletion or inactivation of T cells and HIV replication may be important factors in the clinical evolution of HHV-8 infection and the development of KS [ 4 , 29 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, mannose-binding lectin (MBL) plays a key role in innate immunity as a standard recognition receptor, binding with a high affinity to the residue patterns of carbohydrates present on the surface of viruses or virus-infected cells, especially when the humoral immunity is not fully functional, such as in childhood or in immunosuppressed or immunocompromised populations [1315]. Thus, MBL contributes to the defence of the innate immune system by initiating the activation of the lectin-complement pathway, which promotes opsonophagocytosis, modulates inflammation and induces cellular lysis [16–18].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding PLWHA, some studies have shown an association between MBL plasma concentration deficiency and HIV infection or a more rapid disease progression [19–23], and others found no association with this infection, the HIV viral load or the CD4 count [18, 24]. However, the influence of MBL on HHV-8 infection is not known, but for other herpes viruses, studies suggest that MBL deficiency may be a risk factor for the symptomatic development of human herpesvirus 2 (HHV-2) [25] and for cytomegalovirus reactivation (CMV) [14, 26].…”
Section: Introductionmentioning
confidence: 99%